Pelatihan Emergency Response Plan Di Fame Hotel Gading Serpong Tangerang - Kurniawan, Wahyu; Gunawan, Fandhy; Tri Saputra, Surya; Kalbuana, Nawang; Yusmana, Wawan; Supri, Supri; Wahyudono, Wahyudono (Jurnal Pengabdian Kepada Masyarakat, 2024)
An Emergency Response Plan is an action that has been planned to minimize casualties and losses when a disaster occurs. Disasters that occur can include earthquakes, fires, floods, and even bomb threats that cannot be predicted when the disaster will occur. It is very important to implement ERP in public buildings, one of which is hotels. Indonesian Civil Aviation Polytechnic Curug, as a form of the Tri Darma of Higher Education, provides community service through Emergency Response Plan training. The aim of this activity is to provide training participants with knowledge regarding handling emergency situations. Participants consisted of 20 employees from several hotels in the Gading Serpong area. The result of this activity is an increase in knowledge of emergency response plans. Apart from that, the activity ran smoothly and could be categorized as very good based on the results of the questionnaire at the end of the training.